2004
DOI: 10.1093/hmg/ddh322
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study and transmission disequilibrium test provide consistent evidence for association between schizophrenia and genetic variation in the 22q11 gene ZDHHC8

Abstract: Genetic variants in the 22q11 gene ZDHHC8, which encodes a putative transmembrane palmitoyltransferase, has been associated to schizophrenia in family-based linkage disequilibrium (LD) studies. The single nucleotide polymorphism (SNP) rs175174 (A/G), which had the strongest association, has been shown recently to regulate the level of the fully functional transcript by modulating the retention of intron 4 of ZDHHC8. In this work, we genotyped three genetic variants within the ZDHHC8 locus and conducted associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 19 publications
1
51
1
Order By: Relevance
“…In order to detect the reliability of our platform, we evaluated it with several published scientific papers [2][3][4][5][6] and obtained exactly the same result but very robust rate. Compared with the tools used in cited papers [2][3][4][5][6], our platform shows the advantage of easier handling and the capability of analyzing complicated data.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In order to detect the reliability of our platform, we evaluated it with several published scientific papers [2][3][4][5][6] and obtained exactly the same result but very robust rate. Compared with the tools used in cited papers [2][3][4][5][6], our platform shows the advantage of easier handling and the capability of analyzing complicated data.…”
Section: Resultsmentioning
confidence: 94%
“…Compared with the tools used in cited papers [2][3][4][5][6], our platform shows the advantage of easier handling and the capability of analyzing complicated data. Therefore, it could become a powerful and useful tool for studies of complex diseases in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…The biologic effects of this allele on the abundance and function of the enzyme are unknown. Other studies have not confirmed the association of rs175174 with schizophrenia (Faul et al 2005;Glaser et al 2005;Otani et al 2005;Saito et al 2005) or have shown an association of the rs175174G, not the A allele, with schizophrenia (Chen et al 2004b). The role of ZDHHC8 in 22q11DS-schizophrenia is unclear.…”
Section: Linkage and Association Studiesmentioning
confidence: 96%
“…326 Subsequent studies have confirmed positive associations between mutations in ZDHHC8 and schizophrenia across a number of racial groups, as well as a sex-related heterogeneity of allele transmission, whereby female patients showed a stronger association between mutations in ZDHHC8 and schizophrenia. 325,327 However, multiple studies have been unable to replicate these findings across various racial groups, although modest evidence of a sex-related heterogeneity of allele transmission has been confirmed. 328,329 Whereas ZDHHC8 is a positional candidate gene, no endophenotypes have been associated with it and, given the inconsistent results, it is difficult to make a conclusive determination about its role in the development of schizophrenia.…”
Section: Zinc Finger Dhhc-type Containing 8 (Zdhhc8)mentioning
confidence: 99%